2021
DOI: 10.1002/ctm2.634
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus lactis and Pediococcus pentosaceus‐driven reprogramming of gut microbiome and metabolome ameliorates the progression of non‐alcoholic fatty liver disease

Abstract: Background Although microbioa‐based therapies have shown putative effects on the treatment of non‐alcoholic fatty liver disease (NAFLD), it is not clear how microbiota‐derived metabolites contribute to the prevention of NAFLD. We explored the metabolomic signature of Lactobacillus lactis and Pediococcus pentosaceus in NAFLD mice and its association in NAFLD patients. Methods We used Western diet‐induced NAFLD mice, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 61 publications
3
33
0
Order By: Relevance
“… 493 Lactobacillus lactis and Pediococcus pentosaceus also restored metabolite dysregulation in the gut of western diet‐induced NAFLD mice. 494 …”
Section: Novel Signaling Pathways and Pharmacological Targetsmentioning
confidence: 99%
“… 493 Lactobacillus lactis and Pediococcus pentosaceus also restored metabolite dysregulation in the gut of western diet‐induced NAFLD mice. 494 …”
Section: Novel Signaling Pathways and Pharmacological Targetsmentioning
confidence: 99%
“…A study focusing on the role of the microbiome in obesity and diabetes in humans and rodents revealed significant differences of gut microbiota between lean and obese subjects, most notably an increased F/B ratio in obesity subjects ( Ley et al., 2006 ). Analysis of non-alcoholic fatty liver disease patients also showed an elevated F/B ratio compared with healthy control ( Yu et al., 2021 ). In addition, higher risk of breast cancer recurrence was reported to be associated with lower F/B ratio ( Okubo et al., 2020 ).…”
Section: Discussionmentioning
confidence: 94%
“…Studies have demonstrated that the gut microbiota is involved in NAFLD disease progression with complex roles ( Brandl and Schnabl, 2017 ). Yu et al (2021) used GC-MS, LC-MS and other metabolomics analysis methods to detect the cecal metabolic profile of NAFLD mice and the fecal metabolic profile of NAFLD patients. They found that compared with normal controls, NAFLD patients and NAFLD mice had intestinal metabolites and microbial communities were significantly changed.…”
Section: Application Of Metabolomics In the Treatment Of Nafldmentioning
confidence: 99%